INTEGRATION OF DOMESTIC TRANSPORT INFRASTRUCTURE INTO THE GLOBAL LOGISTICS SYSTEM - FALOVYCH, Volodymyr; FALOVYCH, Nataliia; SHEVCHUK, Oksana; YAKYMYSHYN, Liliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the problems of integrating the domestic transport infrastructure into the global logistics system, in particular in the context of constant challenges associated with military operations. The authors highlight a number of important aspects that determine the potential of Ukraine as a strategic transport hub between Europe and Asia. One of the main factors is the geographical location of the country, which provides the opportunity to use key international transport corridors that are important for the development of global supply chains. However, despite these advantages, the Ukrainian transport infrastructure faces serious problems that limit its integration into international transport networks. Among them, the authors note the outdated material and technical base, damage to the infrastructure as a result of hostilities, the low quality of road and railway routes, imperfect port equipment, and problems with customs procedures. The war significantly complicates the functioning of existing transport routes, which reduces Ukraine’s competitiveness in the international transport market and hinders investment attraction.Taking into account global trends in the development of transport systems, the article focuses on the need to modernize Ukrainian infrastructure in accordance with international standards. The authors propose a number of strategic steps, including the creation of multimodal logistics hubs, which will optimize cargo flows and increase the efficiency of transport. An important component of these initiatives is the development of intelligent transport systems (ITS) and the digitalization of logistics processes, which can significantly reduce operating costs, increase the speed of cargo processing and reduce administrative barriers. Attention is also paid to the issues of harmonizing national legislation with international and European standards, which is an important element for attracting foreign investment in the modernization of transport infrastructure. An important aspect is also the improvement of the regulatory environment, which will simplify customs procedures, increase the safety of transport routes and create a favorable investment climate.In general, the authors emphasize that for the effective integration of Ukraine into the global logistics system, a comprehensive approach is needed, which includes not only the technical upgrade of the infrastructure, but also the political will to reform administrative procedures, in particular in the area of customs and certification. They believe that only under the conditions of cooperation between state bodies, the private sector and international partners can the full potential of Ukraine as an important element of international transport corridors be achieved.
Keywords: global logistics system; international transport corridors; optimization of cargo flows; attraction of foreign investments; integration of transport infrastructure; strategic geographical location; modernization of infrastructure